Understanding and treating hypertension in diabetic populations - Volpe, Massimo (Cardiovasc Diagn Ther, 2015)
Hypertension and diabetes frequently occurs in the same individuals in clinical practice. Moreover, the presence of hypertension does increase the risk of new-onset diabetes, as well as diabetes does promote development of hypertension. Whatever the case, the concomitant presence of these conditions confers a high risk of major cardiovascular complications and promotes the use integrated pharmacological interventions, aimed at achieving the recommended therapeutic targets. While the benefits of lowering abnormal fasting glucose levels in patients with hypertension and diabetes have been consistently demonstrated, the blood pressure (BP) targets to be achieved to get a benefit in patients with diabetes have been recently reconsidered. In the past, randomized clinical trials have, indeed, demonstrated that lowering BP levels to less than 140/90 mmHg was associated to a substantial reduction of the risk of developing macrovascular and microvascular complications in hypertensive patients with diabetes. In addition, epidemiological and clinical reports suggested that “the lower, the better” for BP in diabetes, so that levels of BP even lower than 130/80 mmHg have been recommended. Recent randomized clinical trials, however, designed to evaluate the potential benefits obtained with an intensive antihypertensive therapy, aimed at achieving a target systolic BP level below 120 mmHg as compared to those obtained with less stringent therapy, have challenged the previous recommendations from international guidelines. In fact, detailed analyses of these trials showed a paradoxically increased risk of coronary events, mostly myocardial infarction, in those patients who achieved the lowest BP levels, particularly in the high-risk subsets of hypertensive populations with diabetes. In the light of these considerations, the present article will briefly review the common pathophysiological mechanisms, the potential sites of therapeutic interactions and the currently recommended BP targets to be achieved under pharmacological treatment in hypertension and diabetes.